On reading some of Karl Barth's early sermons in South Africa today? - M. Laubscher (Acta Theologica)
The work of Karl Barth has been quite influential in South Africa, but what about the value of his sermons and their influence on Barth’s reading and mainline preaching in South Africa nowadays? After a short introduction, I discern, in four sections, the value and worth of reading Barth’s early sermons in South Africa at present. I first hear anew the value of reading Barth in South Africa nowadays. Thereafter, I discern the current state of homiletics. Against this background, I pay attention critically to some of Barth’s early sermons (1917-1920) while he was still a minister in Safenwil. Finally, I discern some of the value this project may currently have for theology and preaching in South Africa.